The Effect of Maternal Attitude on the Evaluation of Behavioral Feeding - Ozturk, Elif Esra; Ozgen, Leyla (International Journal of Child Health and Nutrition, 2022)
Introduction: This study was planned to determine maternal attitudes' effect on behavioral pediatric feeding assessment in mothers with children aged 6-9 years. Methods: The sample consisted of 196 mothers with children aged 6-9 years. The Behavioral Pediatric Feeding Assessment Scale and the Hamel Maternal Attitude Scale were employed to assess behavioral pediatric feeding and maternal attitudes, respectively. Results: A significant correlation was found between the Behavioral Pediatric Feeding Assessment Scale total scores and the “authoritarian” subscale of the Hamel Maternal Attitude Scale. There were significant differences in the participants’ Behavioral Pediatric Feeding Assessment Scale scores in terms of children's ages and family types. Conclusion: As a result, it was determined that the mother's feeding behavior of her child is affected by both the factors related to her child, the environment in which she lives, and her own attitude.